Exchange rate dynamics and monetary policy: Evidence from a non-linear DSGE-VAR approach - Florian Huber; Katrin Rabitsch (University of Salzburg, Department of Social Sciences and Economics, 2019)
In this paper, we reconsider the question how monetary policy influences exchange rate dynamics. To this end, a vector autoregressive (VAR) model is combined with a two-country dynamic stochastic general equilibrium (DSGE) model. Instead of focusing exclusively on how monetary policy shocks affect the level of exchange rates, we also analyze how they impact exchange rate volatility. Since exchange rate volatility is not observed, we estimate it alongside the remaining quantities in the model. Our findings can be summarized as follows. Contractionary monetary policy shocks lead to an appreciation of the home currency, with exchange rate responses in the short-run typically undershooting their long-run level of appreciation. They also lead to an increase in exchange rate volatility. Historical and forecast error variance decompositions indicate that monetary policy shocks explain an appreciable amount of exchange rate movements and the corresponding volatility.
Keywords: E43; E52; F31; 330; monetary policy; Exchange rate overshooting; stochastic volatility modeling; DSGE priors